COMPLICATIONS CAUSED BY IRON DEFICIEN ANEMIA DURING PREGNANCY AND THE IMPORTANCE OF CLINICAL-LABORATORY DIAGNOSIS - Silva, Carla Cristina; Amancio da Silva Júnior, Izamar; Barbo de Oliveira, João Vitor; Chagas Belarmino, Thais Giovana; Borges Macàªdo, Guilherme (CIPEEX, 2024)
Anemia is defined according to hemoglobin levels, which can vary according to many factors, mainly age, sex and ethnicity. The impacts of anemia during pregnancy involve negative effects on maternal health that can lead to death and death on fetuses. Laboratory evaluation is essential for the definitive diagnosis of iron deficiency and early treatment. The study aims to describe the impacts of maternal anemia and iron deficiency during pregnancy, as well as the clinical and laboratory diagnosis of the pathology. This is a narrative review of the literature. Scientific articles will be analyzed on Google Scholar and in the databases PUBMED, SCIELO (Scientific Electronic Library Online), MEDLINE (National Library of Medicine) published between 2018 and 2023, selected from the titles that contain references to the descriptors. Research has shown that it is important to have an adequate balance of body iron for well-being and quality of life. In pregnant women, it is necessary to have good iron levels for a good outcome of the pregnancy, for the mother's well-being and for the normal development of the fetus and maturity of the newborn. Oral iron supplementation is the first line of treatment in cases of mild anemia, however, considering the numerous gastrointestinal side effects that often lead to poor adherence, other therapeutic strategies should be evaluated. More efforts must be devoted by the prenatal healthcare system to eradicate this significant problem, as children born to iron-deficient mothers are susceptible to various health problems.